Health consequences of the US Deferred Action for Childhood Arrivals (DACA) immigration programme: a quasi-experimental study - Atheendar S Venkataramani, DrMD; Sachin J Shah, MD; Rourke O'Brien, PhD; Ichiro Kawachi, ProfPhD; Alexander C Tsai, MD (Elsevier, 2017)
Summary: Background: The effects of changes in immigration policy on health outcomes among undocumented immigrants are not well known. We aimed to examine the physical and mental health effects of the Deferred Action for Childhood Arrivals (DACA) programme, a 2012 US immigration policy that provided renewable work permits and freedom from deportation for a large number of undocumented immigrants. Methods: We did a retrospective, quasi-experimental study using nationally representative, repeated cross-sectional data from the US National Health Interview Survey (NHIS) for the period January, 2008, to December, 2015. We included non-citizen, Hispanic adults aged 19-50 years in our analyses. We used a difference-in-differences strategy to compare changes in health outcomes among individuals who met key DACA eligibility criteria (based on age at immigration and at the time of policy implementation) before and after programme implementation versus changes in outcomes for individuals who did not meet these criteria. We additionally restricted the sample to individuals who had lived in the USA for at least 5 years and had completed high school or its equivalent, in order to hold fixed two other DACA eligibility criteria. Our primary outcomes were self-reported overall health (measured on a 5 point Likert scale) and psychological distress (Kessler 6 [K6] scale), the latter was administered to a random subset of NHIS respondents. Findings: Our final sample contained 14 973 respondents for the self-reported health outcome and 5035 respondents for the K6 outcome. Of these individuals, 3972 in the self-reported health analysis and 1138 in the K6 analysis met the DACA eligibility criteria. Compared with people ineligible for DACA, the introduction of DACA was associated with no significant change among DACA-eligible individuals in terms of self-reported overall health (b=0·056, 95% CI −0·024 to 0·14, p=0·17) or the likelihood of reporting poor or fair health (adjusted odds ratio [aOR] 0·98, 95% CI 0·66-1·44, p=0·91). However, DACA-eligible individuals experienced a reduction in K6 score compared with DACA-ineligible individuals (adjusted incident risk ratio 0·78, 95% CI 0·56-0·95, p=0·020) and were less likely to meet screening criteria for moderate or worse psychological distress (aOR 0·62, 95% CI 0·41-0·93, p=0·022). Interpretation: Economic opportunities and protection from deportation for undocumented immigrants, as offered by DACA, could confer large mental health benefits to such individuals. Health consequences should be considered by researchers and policy makers in evaluations of the broader welfare effects of immigration policy. Funding: None.